Local Transmigration Program in Merauke Regency - Edoardus E. Maturbongs (Public Policy and Management Inquiry, 2025)
The lives of local communities in Papua require government attention amidst modernization and development through various programs, one of which is the transmigration program. The purpose of this study is to describe the local transmigration program in Merauke Regency. This study used a qualitative approach, collecting data through observation, interviews, and literature review. The data were then analyzed using the NVivo 15 analysis tool. The research results show that the transmigration program in Merauke Regency is currently being implemented using a local transmigration approach, focusing on local villages within the Regency, where the transmigration areas are the customary rights of the communities. The existence of the local transmigration program has had an impact on the lives of local communities, such as the construction of various infrastructure to support the program. The implication of this research is that local governments need to adopt a different approach to successfully implement the local transmigration program.